"Scrounger-bashing" as national pastime: the prevalence and ferocity of anti-welfare ideology on niche-interest online forums. Issue 3 (27th May 2021) - Morrison, James
ABSTRACT: Recent research has noted the persistence of a long continuum of "anti-welfare" discourses that are increasingly embedded in the UK news media, political communication, and popular culture (e.g. Golding and Middleton 1982 . Images of Welfare: Press and Public Attitudes to Poverty . Oxford: Mark Robertson; Jensen 2014 . "Welfare Commonsense, Poverty Porn and Doxosophy." Sociological Research Online 19 (3): 277–283; Morrison 2019. Scroungers: Moral Panics and Media Myths . London: Zed Books). Historical distinctions between the "deserving" and "undeserving poor" have been sharpened by successive governments in the service of varying shades of neoliberal governance. While Margaret Thatcher castigated "shirkers" in fostering an ideology of economic self-reliance, both New Labour and the Coalition obsessed over "welfare reform": promoting an ideology of "work" in symbolic opposition to supposed cultures of "worklessness". But, while "scroungerphobia" (Deacon 1978 . "The Scrounging Controversy: Public Attitudes Towards the Unemployed in Contemporary Britain." Social Policy and Administration 12 (2): 120–135) is now a widely recognised sociological phenomenon, scholarly attention to the concept has largely been reserved for its manifestation in tabloid newspapers, political rhetoric and, latterly, "poverty porn" television. Even recent work considering the public's contribution to scrounger discourse(s) on social media focuses on mainstream platforms, such as Twitter and newspaper comment threads (e.g. Van Der Bom et al. 2018 . "'It's not the Fact They Claim Benefits but Their Useless, Lazy, Drug Taking Lifestyles we Despise': Analysing Audience Responses to Benefits Street Using Live Tweets." Discourse, Context & Media 21: 36–45; Morrison 2019. Scroungers: Moral Panics and Media Myths . London: Zed Books; Paterson 2020 ). This paper begins to address this oversight, by examining how normative anti-welfare discourses infiltrate everyday communication in more disparate online communities – including niche consumer forums. It draws on previously unpublished findings from an analysis of welfare-related conversations in these and other spaces at the height of a recent moral panic over "scroungers": the period from 2013-2016, when Conservative-led governments strove to legitimise sweeping benefit cuts and punitive "welfare reform".